Pharmacological inhibition of IL12β is effective in treating pressure overload-induced cardiac inflammation and heart failure - Bhattarai, Umesh; He, Xiaochen; Niu, Ziru; Pan, Lihong; Wang, Dongzhi; Wang, Hao; Zeng, Heng; Chen, Jian-Xiong; Speed, Joshua S.; Clemmer, John S.; Chen, Yingjie (Frontiers in Immunology, 2025)
Background and objectiveEmerging evidence indicates that inflammation regulates cardiac remodeling and heart failure (HF). IL12β is a subunit for proinflammatory cytokines IL12 and IL23. However, the effect of IL12β inhibition on HF development and the underlying mechanism is not understood.MethodsWe determined the effect of pharmacological inhibition of IL12β using IL12β blocking antibody on transverse aortic constriction (TAC)-induced left ventricular (LV) inflammation and HF development.ResultsIL12β blocking antibody significantly attenuated TAC-induced LV immune cell infiltration, hypertrophy, fibrosis, dysfunction, and the consequent pulmonary inflammation and remodeling. More specifically, we found that IL12β blocking antibody significantly attenuated TAC-induced LV and pulmonary infiltration of neutrophils, macrophages, CD11c+ dendritic cells, CD8+ T cells, and CD4+ T cells. Moreover, IL12β blocking antibody significantly suppressed the production of pro-inflammatory cytokine pro-IL1β and IFNγ by macrophages and IFNγ by CD8+ T cells and/or CD4+ T cells.ConclusionsThese findings indicate that pharmacological inhibition of IL12β effectively protected the heart from systolic overload-induced inflammation, remodeling, and dysfunction by reducing the proinflammatory signaling from both innate and adaptive immune responses.